Determinants of Systematic Risk : Empirical Evidence from Shariah Compliants Firms Listed on Bursa Malaysia - Jaafar, Mohamad Nizam; Muhamat, Amirul Afif; Basri, Mohd Faizal; Syed Alwi, Sharifah Faigah (International Business Education Journal, 2020)
This paper is aimed at advancing empirical indications on micro variable factors determining systematic risk in Shariah complaints firms listed on Bursa Malaysia. This paper also attempts to identify whether the Shariah compliant firms are showing the same micro variables factors that determine systemic risk. The systematic issues have become the main concern to many related parties such as policy makers, investors and stakeholders as systematic risk is unable to be removed through diversification. Shariah compliant firms have their own unique systematic risk owing to their difference in business philosophy. A hypothesis between the relationship of the firms-specific micro variable factors and systemic risk are established on foregoing studies and theoretical framework respectively, and analyzed using the Fixed Effects Model tested on the data from 80 listed companies covering a period from 2009 to 2018. The results show that leverage and growth are the most significant factors of the systematic risk of Shariah compliant firms. Therefore, high leverage and growth firms are considered to be high risk for investment in Malaysia capital market.